Fazno konjugirajoča ogledala - Pušavec, Žiga (Matrika, 2018)
A Phase Conjugate Mirror reflects an incoming wave so that the reflected wave exactly follows the path it has previously taken - this can be interpreted as rewinding the time. This counterintuitive phenomenon has many interesting applications in correction of aberration that appear due to imperfect optical elements in fields of high energy lasers, optical communications and optical circuits. The origin of the phenomenon lies in the third order nonlinear optical response of matter. Two main mechanisms are discussed: degenerate four-wave mixing and stimulated Brillouin backscattering.
Keywords: fazna konjugacija; mirrors; nelinearna optika; nonlinear optics; odboj svetlobe; phase conjugation; reflection; zrcala